Distribution of pesticides in agroecosystem food webs differ among trophic groups and between annual and perennial crops - Michalko, Radek; Purchart, Luboš; Hofman, Jakub; Košulič, Ondřej (Springer France, 2024)
Pesticides threaten biodiversity, but we know little about how they permeate food webs. Few studies have investigated the number, concentration, and composition of pesticides in agroecosystem food webs even though agroecosystems cover one-third of Earth's land area. We conducted a pioneering study on the distribution of pesticides across local (i.e., on farm) and meta food webs (i.e., regional pool of local food webs) within both perennial (N = 8) and annual crops (N = 11), examining four trophic groups-soil (primary resource), plants (primary producers), rodents (herbivores), and spiders (predators)-for the presence of multiple residues, and comparing these findings to pesticides applied by farmers in recent years. We also undertook interviews with farmers to obtain the most precise information about pesticide applications in their fields. We detected a wide spectrum of pesticides in both annual and perennial crop types. Pesticides applied by farmers represented only a small proportion of all detected pesticides, indicating that pesticides entered local food webs from surrounding landscapes. Some detected pesticides had been banned by the European Union several years ago, which is highly alarming. Trophic group mobility and crop type drove pesticides number at local scale, as mobile groups contained larger numbers of pesticides (probably from encountering wider spectra of pesticides). At a meta scale, spiders contained the highest number of detected pesticides in perennial crops but lowest diversity in annual crops. This might be explained by how spiders' functional traits are selected in different crops. Insecticides and fungicides concentrations mostly increased with trophic level, indicating bioaccumulation. Herbicides concentration were highest in plants suggesting (bio)degradation. As bioaccumulation outweighed (bio)degradation, pesticides increased overall with trophic level. Therefore, the distribution of pesticides in agroecosystem food webs was affected simultaneously by several mechanisms and depended upon trophic group, crop type, and, probably, surrounding landscape.
Keywords: Bioaccumulation; Fungicide; Herbicide; Insecticide; Plant; Rodent; Soil; Spider